Problematika Pengembangan Karakter Peserta Didik di Era 4.0 - Hendayani, Meti (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2019)
Character education is an effort in dealing with the various challenges that the shifts from character are facing today. The purpose of character education is to develop various abilities of students to make good and bad decisions, maintain good values ​​and make them happen in everyday life in home, school, or in a community environment. However, in the era of industrial revolution 4.0 or known as the millennial generation, there have been various problems that inhibit the development of character education for students. These problems include the origin of the students themselves (internal factors) and from outside (external factors). Internal factors include instincts, habits, heredity, desire or willpower and conscience. While the external factors are promiscuity, the influence of gadgets, the negative influence of television, family and school.